2021
DOI: 10.3389/fcell.2021.801507
|View full text |Cite
|
Sign up to set email alerts
|

Septins in Stem Cells

Abstract: Septins were first described in yeast. Due to extensive research in non-yeast cells, Septins are now recognized across all species as important players in the regulation of the cytoskeleton, in the establishment of polarity, for migration, vesicular trafficking and scaffolding. Stem cells are primarily quiescent cells, and this actively maintained quiescent state is critical for proper stem cell function. Equally important though, stem cells undergo symmetric or asymmetric division, which is likely linked to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 124 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…As biotransformation enzymes, they play an important role in cellular antioxidant defence mechanisms by catalyzing the reduction of potentially harmful peroxides. 72 They can lead to chondrogenic or adpogenic differentiation of mesenchymal cells. In addition, microfibrillar-associated protein 2 and Fascin have previously been associated with the activation and inhibition of osteogenic differentiation of HMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As biotransformation enzymes, they play an important role in cellular antioxidant defence mechanisms by catalyzing the reduction of potentially harmful peroxides. 72 They can lead to chondrogenic or adpogenic differentiation of mesenchymal cells. In addition, microfibrillar-associated protein 2 and Fascin have previously been associated with the activation and inhibition of osteogenic differentiation of HMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In MG63-derived ExosNPs, we identified 8 different proteins, and interestingly, most have already been described as having osteogenic activity on HMSCs. [70][71][72][73][74][75][76] Among these proteins, we highlight alpha N-acetylglucosaminidase, which has already been described as modulating the negative effect of several transcription effectors including methylation of the transcription factor Runx2. 75,76 Runx2 is the master switch controlling osteoblast differentiation and mineralized skeleton formation.…”
Section: Papermentioning
confidence: 99%
“…It is known that Cdc42 activity is connected to polarity but how the spatial rearrangements in HSCs upon aging occur remains under investigation. As there are changes in the Cdc42-Borg4-Septin7 axis upon aging [21] and Septin7 belongs to a group of cytoskeletal proteins known for polarity regulation and maintenance (Septins) [27] we hypothesized spatial changes in the 13 distinct Septin proteins of mice which form a network that is critical for the compartmentalization of cell content and thus polarity [30]. CellDetail, analyzing data from a novel six Septin IF staining in single cells, revealed a less focused overall organization of the Septin network within aged HSCs.…”
Section: Mainmentioning
confidence: 99%
“…Septins interact with Actin and Tubulin. They compartmentalize cells by forming hetero-oligomeric complexes and filaments which serve as scaffolds for protein recruitment or as diffusion barriers [27,30]. There are 13 Septins in mammals, which are classified into four SEPT groups based on homology: SEPT2 (Septin1, Septin2, Septin4, Septin5), SEPT3 (Septin3, Septin9, Septin12), SEPT6 (Septin6, Septin8, Septin10, Septin11, Septin14) and SEPT7 (Septin7).…”
Section: Quantification Of the Level Of Polarity Of Cdc42 Andmentioning
confidence: 99%
“…For example, Mo et al [56] demonstrated that changes in ctDNA may enable us to detect residual disease, guide chemotherapy, stratify risk, and monitor recurrence of stage I to III colorectal cancer. They performed multiplex ctDNA methylation and quantitative polymerase chain reaction assay to detect the ctDNA of six biomarkers (SEPTIN9 locus 1, BCAT1, IKZF1, SEPTIN9 locus 2, VAV3, and BCAN), which in one way or another implicated stem-like or stemness properties, i.e., pluripotency, self-renewal, and differentiation of progenitor stem cells in various tissues [57][58][59][60][61][62].…”
Section: Monitoringmentioning
confidence: 99%